Meditations on teaching drawing and movement as 'mind in motion'. Issue 1 (1st April 2023) - Simmons, Seymour
In this paper, I take the theme 'Drawing and Movement' as an opportunity to reflect on relationships between mind and body in learning how to draw as fostered by diverse teaching methods. Towards that end, I initially propose a cognitive perspective based on BarbaraTversky's 2019 book, Mind in Motion, then apply it to two movement-intensive drawing skills – mark or pattern-making and figurative sketching, each with an imperative for practice. In the process, the concept of 'mind in motion' helps shed new light on five instructional paradigms I defined in my previous research. To conclude, I review conditions in contemporary culture and visual arts education that make the restoration of drawing instruction as outlined here especially relevant in the digital age. Connecting these sections, I will highlight eight drawing demonstrations to illustrate how 'mind in motion' helps explain how drawing not only represents thought in different domains (art, science, philosophy, etc.) but in fact facilitates it.